Do MTurkers Exhibit Myopic Loss Aversion? - Rene Schwaiger; Laura Hueber (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We present results from a highly powered online experiment with 937 participants on Amazon Mechanical Turk (MTurk) that examined whether MTurkers exhibit myopic loss aversion (MLA). The experiment consisted of measuring MLA-compliant behavior in two between-subjects treatments that differed only regarding the risk profile of the risky asset employed. We found no statistically significant evidence of MLA-compliant behavior among MTurkers in both treatments.
Keywords: G10; G11; G41; 330; online experiment; myopic loss aversion; risk; mturk